Linking soils to ecosystem services — A global review - Adhikari, Kabindra; Hartemink, Alfred E. (Geoderma, 2016)
Soil plays a crucial role in ecosystem functioning. In the 1990s ecosystem services (ES) research focused on developing the concept and framework and only a few studies linked soil properties to ecosystem services. This study reviews the literature on the relationship between soils and ecosystem services and aims to contribute to the scientific understanding on soil and ecosystem services and their interrelations. Most studies have focused on provisioning and regulating ES relating to soil physico-chemical properties. Cultural services had only a few studies, and supporting services were mostly related to soil physico-chemical and biological properties. The number of ES papers increased rapidly after 2000 and in the past 5years, regulating services such as carbon sequestration, climate and gas regulations, were commonly studied. Once the concept was established in the 1990s, studies focusing on the assessment, valuation, and payments of services became more prominent. Most soil-ES research is published in Geoderma. Soil scientists seems to be hesitant to use the term ‘ecosystem services’ even if their research is devoted to linking soils to ecosystem services. We suggest that future ES research should focus on exploring soil functional diversity of soil biota and the spatial aspects of soil properties to lower level ecosystem services (e.g., water purification, gene pool, and climate regulation). Soil scientists should engage professionals from other disciplines to further promote the contribution of soils to ecosystem services delivery and human well-being. ES soil studies could be used in local and national policy development and program on natural resource use and management. [Display omitted] •Contributes to the understanding of soils in relation to ecosystem services (ES)•Temporal and geographical distribution of soil ES studies has been analyzed.•Highlights use of soil information on the spatial aspects of soil ES studies•Recommends the future soil ES research focus